2010
DOI: 10.1021/ja1084578
|View full text |Cite
|
Sign up to set email alerts
|

Active Site Environment of Heme-Bound Amyloid β Peptide Associated with Alzheimer’s Disease

Abstract: Recent reports show that there is a large increase in heme in the temporal brain of Alzheimer's disease (AD) patients, as heme, biosynthesized in brain cells, binds to amyloid β (Aβ), forming heme-Aβ complexes. This leads to the development of symptoms that are characteristic pathological features of AD, e.g., abnormal iron homeostasis, decay of iron regulatory proteins, dysfunction in mitochondrial complex IV, oxidative stress, etc. However, the active site resulting from heme binding to Aβ is not well charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
220
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(233 citation statements)
references
References 38 publications
13
220
0
Order By: Relevance
“…1B). The result further indicated that the hydrophilic N-terminal of Ab was involved in heme binding [16][17][18], and played an important role in promoting the peroxidase activity of heme. This peroxidase activity of Ab-heme complexes (with k obs of 4.2 Â 10 À3 min À1 ) was $3 times faster compared to that of free heme (with k obs of 1.5 Â 10 À3 min À1 ), similar to a previous study [16].…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…1B). The result further indicated that the hydrophilic N-terminal of Ab was involved in heme binding [16][17][18], and played an important role in promoting the peroxidase activity of heme. This peroxidase activity of Ab-heme complexes (with k obs of 4.2 Â 10 À3 min À1 ) was $3 times faster compared to that of free heme (with k obs of 1.5 Â 10 À3 min À1 ), similar to a previous study [16].…”
Section: Resultsmentioning
confidence: 81%
“…His residues were essential in peroxidase activity of Ab-heme complexes It is well-known that heme binds to Ab peptides in the hydrophilic portion (residues 1-16) and His residues are found to be the possible binding ligands [16][17][18]. Thus, Ab 1À40 , Ab 1À16 and Ab 17À40 fragments were used to investigate the possible relationship between histidine-bound complex and peroxidase-like active site.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent evidence shows that Aβ can induce intracellular heme synthesis and iron uptake in vitro [9,32] . Heme can bind to Aβ to form heme-Aβ, promoting [24,26,33,34] .…”
Section: Discussionmentioning
confidence: 99%